#AASW7 vlog: Interview with Wellington Ekaya, ILRI BecA hub - Ekaya, Wellington N. (Forum for Agricultural Research in Africa, 2016)
This vlog is part of the onsite reporting from the #AASW7 social media team. The video was recorded and edited by Assetou Diarra, one of our social reporters